VOLUME 5, NO 1 (2017) - Editor In Chief (ARO-The Scientific Journal of Koya University, 2017)
Dear readers, you are holding the eighth issue (Vol V, No 1) of Aro the Scientific Journal of Koya University in your hand. Aro is publishing its 3rd issue as an internationally listed Scientific Journal in Kurdistan Region/Iraq. Notably, Aro has been accepted for indexing in the Emerging Sources Citation Index (ESCI), a new edition of Web of Science™ as of Feb 2016. Content in this index is under consideration by Thomson Reuters to be accepted in the Science Citation Index Expanded™ (SCIE). Aro’s individual articles are currently listed by Thomson Reuters using articles unique DOI numbers which is a historical achievement for our academic community. Aro is starting its fifth year journey in leading the quality of regional scientific publications with global impact. The editorial team is determined to keep the path of such a mission and sustain Aro’s future publications with reliable quality in mind.